ANALISIS PENGARUH KETERLIBATAN KERJA DAN PEMBERDAYAAN TERHADAP KEPUASAN KERJA DENGAN MEDIASI JOB CONTENT PLATEAUING ( Studi pada Perangkat Desa se Kecamatan Kandangan Kabupaten Temanggung) - Tri Raharjo, 11.5202.0007 (Students Journal of Economic and Management, 2013)
Job satisfaction has a very important role in the organization. With a high degree of job satisfaction will be able to achieve the objectives of the organization. The purpose of this study was to review and analyze the effect of Work Involvement and Empowerment on Job Satisfaction with the Job Content plateauing mediated by the object of research in a Village Employees atÂ  Sub District Kandangan of Temanggung Regency. The results of multiple regression test can be seen that Work Involvement and Empowerment Variables significantly and negatively related to the Job Content plateauing. Variable Work Involvement and Empowerment positive effect on Job Satisfaction Job Content plateauing while variable significantly and negatively related to Job Satisfaction. From the test results it can be seen that the mediation Job Content plateauing effect has not been proven to mediate Work Involvement and Empowerment on Job Satisfaction Keywords: Job Involvement, Empowerment, Job Satisfaction, and Job Content plateauing